Provincial and Age Disparity on Chronic Disease Education Among Migrants in China: The Migrants Population Dynamic Monitoring Survey. (December 2019) - Guo, Mengdi; Zhu, Zheng; Dong, Tingyue; Mi, Hong; Wu, Bei
Chronic diseases have become serious threats to public health in China; the risk is particularly high for internal migrants. Chronic disease education is a key to the prevention and control of chronic diseases for such population. The national population-based Migrants Population Dynamic Monitoring Survey (MPSMA) was used to examine the current status and delivery methods of chronic disease education among internal migrants, from both provincial level and individual's level. The study population included 402 587 internal migrants. Multilevel logistic regression was used to investigate factors that were related to chronic diseases education. In total, only 33.9% of the participants received chronic disease education. In the final model, parameter estimates on key variables from both individual and provincial level were significant ( P < .001). Participants from provinces with higher level of health care resources and lower density of internal migrants were more likely to receive chronic disease education. The percentage and methods of receiving education varied across different age groups. This study suggests that future chronic disease education in China need to be more focused on areas with high density of internal migrants and younger internal migrants with low level of education and income. Attention should be paid to use tailored education methods to different populations.